Quantitative Analysis of the Competitiveness of Exports of Malanga from Ecuador to the United States - Lizano-Arauz, Carlos David (2022)
Competitiveness and its relationship with science are increasingly narrowing in countries in the process of development, but in developing countries it is a constant in the implementation of public policies for development. Measuring competitiveness will make it possible to understand the current situation of a given economic sector against another, within national borders or beyond. The purpose of this investigation is to analyze the commercial efficiency of malanga as one of the alternative export products in the country's oil sector in the United States, based on the Relative Export Advantage Index (REA) describing the exportable competitiveness of four countries. The result establishes that Nicaragua and Ecuador are competitive in the export of this tuber, while Mexico and the Dominican Republic have not achieved the first levels in the analyzed market, which has an attractive consumption project in the medium market. Additionally, the REA determines the advantages of the US market that has allowed the increase in exports of Ecuadorian malanga, which reflects results in a sector that has traditionally been dominated by traditional historical products, which in this case has not prevented it from being highlighted in a market that is knowing your potential.